Poland anomaly associated with ocular anomalies - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
A 6-year old boy suffering from Poland anomaly has been reported. The patient showed a complete picture of this malformation which consisted of aplastic greater pectoral muscle and breast on the left side of the chest, as well as oligodactily of the left hand.Other anomalies found were ocular and oral anomalies. The ocular anomalies consisted of hypertelorism, bilateral esotropias due to bilateral abducent palsy, and bilateral optic nerve hypoplasia. Oral anomalies consist of the inability to close the mouth properly and the inability to smile may be due to the defect of oral muscles.Key Words: Poland anomaly - chest anomaly - oligodactily - ocular anomalies - oral anomalies